2020
DOI: 10.2147/nss.s272883
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association of Cigarette Smoking with Sleep Disturbance and Neurotransmitters in Cerebrospinal Fluid</p>

Abstract: Background Cigarette smoking has shown to be associated with sleep disturbance, especially prolonged sleep onset latency (SOL). Cigarette smoking stimulates the release of dopamine (DA) and serotonin (5-HT), which might promote awakening and inhibit rapid eye movement sleep. Dopamine transporter (DAT) and serotonin transporter play a key role in the reuptake of DA and 5-HT from the synaptic cleft into presynaptic neurons. However, the relationship among cigarette smoking, sleep disturbance and neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 55 publications
3
15
0
Order By: Relevance
“…Pathological conditions such as Parkinson's, schizophrenia, Huntington's, and attention deficit and hyperactivity disorder have altered levels of dopamine [45]. Increased oxidative stress, such as in smoking, has also been shown to increase levels of both dopamine and serotonin [46]. Likewise, our results show an increase in dopamine (acutely at 3 h) and its rate-limiting enzyme, TyrH.…”
Section: Discussionsupporting
confidence: 69%
“…Pathological conditions such as Parkinson's, schizophrenia, Huntington's, and attention deficit and hyperactivity disorder have altered levels of dopamine [45]. Increased oxidative stress, such as in smoking, has also been shown to increase levels of both dopamine and serotonin [46]. Likewise, our results show an increase in dopamine (acutely at 3 h) and its rate-limiting enzyme, TyrH.…”
Section: Discussionsupporting
confidence: 69%
“…The activation of nicotinic receptors leads to the release of several neurotransmitters, including acetylcholine, dopamine, serotonin, norepinephrine, and gamma-aminobutyric acid. The deleterious effects of nicotine on sleep quality may be attributable to the independent and interactive effects of these neurotransmitters on the central mechanisms that regulate the sleep-wake cycle, resulting in increased sleep latency and contributing to sleep disturbance [ 28 - 30 ]. In addition to the direct action of nicotine on sleep mechanisms, smokers may experience withdrawal symptoms and cravings due to a reduction in their nicotine levels after sleep since the half-life of nicotine in the human body is only 1 hour to 2 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Severe smoking status appears to have a causal effect on the circadian rhythm, and some evidence has shown that insomnia increases smoking heaviness and impedes cessation ( 48 ). Indeed, cigarette smoking has been shown to be associated with sleep disturbance via prolonged sleep-onset latency, higher dopamine levels, and lower dopamine transporter levels in the cerebrospinal fluid of active smokers ( 49 ). The symptoms of cigarette smoking and nicotine dependence were associated with poor sleep quality in young adult smokers ( 50 ).…”
Section: Discussionmentioning
confidence: 99%